Cognitive biases can play a role in extinction assessments: The case of the Caspian tiger - Can, Özgün Emre; D’Cruze, Neil (Frontiers in Ecology and Evolution, 2023)
The premature declaration of a species as extinct has been reported across different taxonomic groups and is commonly referred to as Romeo’s error or the Lazarus effect. In this study, based on a review of historical records and testimonies from local communities, we review the case of Caspian tiger (Panthera tigris virgata), a species we consider was prematurely declared globally extinct in 1950. Considering that compelling evidence which suggests that Caspian tigers probably existed in Turkey perhaps up until early 1990s (some 40 years after international scientific community considered the species extinct) it is reasonable to posit that conservationists missed a historical opportunity to save the species. The case of the Caspian tiger demonstrates the cognitive bias of the Dunning-Kruger effect in action and the potential implications for conservation experts who are engaged in remotely evaluating contemporary species distributions. To mitigate these factors when assessing the global status of species threatened by extinction, we suggest that increased awareness of this type of cognitive bias could facilitate the introduction of additional measures in relevant conservation initiatives. For example, the formation of independent and specific teams to unearth implicit assumptions and weaknesses in assessments, and to question the group thinking of the species assessors. Against the backdrop of the current unprecedented rapid biodiversity decline, we recommend that researchers should be alert of the cognitive biases involved in species assessments and in conservation at large.